OPTIMIZATION OF PROJECT COLOCATION AT PT. XYZ USING PERT AND CPM METHODS BASED ON POM-QM FOR WINDOWS APPLICATION - Eko Purnama; Sugiyono Sugiyono; Ahmad Badawi Saluy (Dinasti Publisher, 2021)
The development of cellular technology continues to increase, so that currently there will be fifth generation (5G) technology. Therefore, the need for telecommunications towers and competition among contractors will increase. The optimization of the colocation project at PT. XYZ has been carried out using the case of the Mekarsari Banjar site, West Java Province using the CPM-PERT method with the POM-QM for Windows application. PERT and CPM methods are methods used to manage project completion time more efficiently and effectively. The result of the research shows that the real project processing time at PT. XYZ on this site for 19 days with a normal fee of Rp. 32,811,000,-. In accelerated conditions, the colocation project can be carried out for 10 days with a Z value = 3.77 with a probability of 99.992% with a total cost of Rp. 34,181,000,- with project effectiveness is around 47.36%.